2014
DOI: 10.1371/journal.pone.0092211
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Reproducibility of Diffusion-Weighted MRI in Monitoring Tumor Response to Neoadjuvant Therapy in Esophageal Cancer

Abstract: ObjectiveTo investigate the reproducibility of diffusion-weighted magnetic resonance imaging (DW-MRI) in assessing tumor response early in the course of neoadjuvant chemoradiotherapy in patients with operable esophageal cancer.MethodsEleven male patients (mean age 54.8 years) with newly diagnosed esophageal cancer underwent DW-MRI before and 10 days after start of chemoradiotherapy. Reproducibility of apparent diffusion coefficient (ADC) measurements by manual (freehand) and semi-automated volumetric methods w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 19 publications
5
30
0
Order By: Relevance
“…One study reported that esophageal squamous cell carcinoma patients with higher initial ADC showed a better response to chemoradiotherapy [31], whereas another study contrarily found significantly higher initial ADC values in non-responders [32]. Similar to our results, a third study found no significant association between initial ADC and response, regardless of a manual or semi-automated ADC measurement in that study [33]. However, our exploratory study suggests that there is some information to gain from the initial ADC value with regard to primary tumor characteristics.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…One study reported that esophageal squamous cell carcinoma patients with higher initial ADC showed a better response to chemoradiotherapy [31], whereas another study contrarily found significantly higher initial ADC values in non-responders [32]. Similar to our results, a third study found no significant association between initial ADC and response, regardless of a manual or semi-automated ADC measurement in that study [33]. However, our exploratory study suggests that there is some information to gain from the initial ADC value with regard to primary tumor characteristics.…”
Section: Discussionsupporting
confidence: 87%
“…This finding has also been recognized in FDG-PET studies for response assessment in esophageal cancer [11,24], and is supported by results from recent DW-MRI studies in rectal cancer [15,39]. In the first study that reported on MRI scanning before and during nCRT in 11 esophageal cancer patients, no correlation was found between change in mean tumor ADC and the histopathologic TRG [33]. However, that study differed from the current study as a smaller sample of patients was studied, a different MRI scan protocol with other b-values was used, other methods for VOI delineation were applied, and patients underwent a different nCRT regimen [33].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Because diffusion within tumor is interrupted by cellular membranes or macromolecular structures, presence or residual tumor cell can be detected as ADC decrease, conversely treatment response can be detected as ADC increase (49). So far, three studies evaluate the benefit of DW-MRI for predicting preoperative treatment (50)(51)(52). A prospective study found that change in ADC during preoperative chemoradiation was associated with pCR (50).…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…A prospective study found that change in ADC during preoperative chemoradiation was associated with pCR (50). One study reported similar result that change in ADC was associated with TRG (52), but another study did not (51). These studies were small, therefore a multi-center study assessing the value of MRI and PET-CT for predicting of preoperative treatment response (NCT02125448).…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%